Koo Nimo: a contemporary Ghanaian musician - Kaye, Andrew L. (International Library of African Music, 1999)
Daniel Kwabena Amponsah, known professionally as Koo Nimo, was born on October 3, 1934 in Ofoase, a village near Kumasi, capital of the Ashanti Region of modem Ghana. His mother, Akua Forkuo, was a farmer, cloth trader, homemaker, and a chorister at the local Methodist church. His father, Kwame Amponsah, was a farmer, tailor, mason, and musical amateur who played the trumpet in the Ofoase brass band.
Keywords: African Music; Ghana